2019
DOI: 10.3390/ma12162533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Printing Parameters on the Fit of Implant-Supported 3D Printing Resin Prosthetics

Abstract: The purpose of the study was to investigate the influence of 3D printing parameters on fit and internal gap of 3D printed resin dental prosthesis. The dental model was simulated and fabricated for three-unit prostheses with two implants. One hundred prostheses were 3D printed with two-layer thicknesses for five build orientations using a resin (NextDent C&B; 3D systems, Soesterberg, The Netherlands) and ten prostheses were manufactured with a milling resin as control. The prostheses were seated and scanned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 35 publications
3
84
0
Order By: Relevance
“…FDM uses a preformed polymer as a building material that uses the input of processing energy in the pre-deposition stage to obtain a polymer melt that can be applied using a fine print head or nozzle [11,17]. Although this study analyzed singe interim restorations by extrapolating the results, the FDPs of the present study obtained minor discrepancy results [16].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…FDM uses a preformed polymer as a building material that uses the input of processing energy in the pre-deposition stage to obtain a polymer melt that can be applied using a fine print head or nozzle [11,17]. Although this study analyzed singe interim restorations by extrapolating the results, the FDPs of the present study obtained minor discrepancy results [16].…”
Section: Discussionmentioning
confidence: 77%
“…The results for the marginal discrepancy of the restorations confectioned at an orientation of 60 • and made of 100 µm-thick layers provided the best mean discrepancy values (50.0 ± 14.7 µm). Nevertheless, it must be noted that most of the 3D printed groups showed worse results than the milled ones [16].…”
Section: Discussionmentioning
confidence: 88%
“…They reported that the SLA technique showed a slightly higher deviation in specific parts of the guide, as compared to the DLP technique, and presented the cause of the difference between the mean deviation of the dental implant position [ 18 ]. Other studies reported that one of the advantages of DLP and SLA printers was less shrinkage as compared to other 3D technologies, including FDM [ 16 , 31 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary for 3D printed dental models to have high dimensional accuracy, while the 3D printing method and specifications that affect surface resolution are also important. Accuracy is determined mostly by the characteristics of SLA, DLP, and FDM printers, but material-related geometry of layer thickness and 3D printing build orientation could also influence the warpage effect and the dimensional accuracy of shrinkage [ 9 , 10 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation